Copper Nitrate Mediated Regioselective [2+2+1] Cyclization of Alkynes with Alkenes: A Cascade Approach to Δ2‐Isoxazolines1. (18th June 2015) - Gao, Mingchun; Li, Yingying; Gan, Yuansheng; Xu, Bin
Abstract An efficient method for the regioselective synthesis of pharmacologically relevant polysubstituted Δ2‐isoxazolines is based on the copper‐mediated direct transformation of simple terminal alkynes and alkenes. The overall process involves the formation of four chemical bonds with inexpensive and readily available copper nitrate trihydrate as a novel precursor of nitrile oxides. The reaction can be easily handled and proceeds under mild conditions.